The in-service non-destructive evaluation of wooden transmission line poles - Prestage, Brendan Paul (Department of Mechanical Engineering, 2016)
This thesis covers the research undertaken on behalf of the ESKOM TRI Group into the In-service Non-Destructive Evaluation of Wooden Transmission Line Poles. The aim of this work was the development of an effective pole tester that could be used to test the integrity of wooden transmission line poles in situ. The pole testing method that ESKOM uses at present is both time and labour intensive and it is envisaged that this research will contribute to the establishment of a faster, cheaper and more effective alternative. The research began with a literature survey of past investigations. Previous research in this area followed two distinct approaches. The first approach concentrated on mechanical testing procedures. For example the physical bending of the pole and measuring its bending stress (the effect that this bending has on the single fibres in the pole is not documented). The present ESKOM pole tester follows this approach. The second approach has been in the field of true "non-destructive" testing. Procedures using x-rays, magnetic resonance imaging and vibration analysis have all been considered in the past by investigators. The present investigation followed the approach of vibrations analysis. The process involved impacting the pole and measuring its vibration response. The response was then used to analyse the pole's behaviour. The state of integrity of the pole determined its vibration characteristics.